2018
DOI: 10.5037/jomr.2018.9305
|View full text |Cite
|
Sign up to set email alerts
|

Is Articaine More Potent than Mepivacaine for Use in Oral Surgery?

Abstract: ObjectivesTo investigate the potency and speed of action of 4% articaine and 2% mepivacaine for maxillary teeth extractions.Material and MethodsNinety-four patients, aged between 16 to 70 years old, were recruited in this study. Two regimens were randomly administered over one visit. Patients of treatment group 1 received mepivacaine 2% with 1:100,000 adrenaline, whereas treatment group 2 - articaine 4% with 1:100,000 adrenaline. The onset time of pulp anaesthesia for maxillary teeth indicated for extraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
2
22
1
2
Order By: Relevance
“…With regard to the anaesthetic onset time, there is a difference between articaine and mepivacaine in which 3.36 minutes and 4.09 minutes were observed, respectively. Moreover, anaesthetic onset times of 2,98 minutes for articaine and 4,22 minutes for mepivacaine were reported elsewhere ( 13 ), which differ from the results found by a clinical study showing that both drugs had a shorter onset time of 2.30 minutes ( 11 ).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…With regard to the anaesthetic onset time, there is a difference between articaine and mepivacaine in which 3.36 minutes and 4.09 minutes were observed, respectively. Moreover, anaesthetic onset times of 2,98 minutes for articaine and 4,22 minutes for mepivacaine were reported elsewhere ( 13 ), which differ from the results found by a clinical study showing that both drugs had a shorter onset time of 2.30 minutes ( 11 ).…”
Section: Discussioncontrasting
confidence: 58%
“…There are a few studies in the literature comparing these anesthetic drugs and showing evidence that both allow a successful pain management ( 11 , 13 , 14 ).When comparing the volume of drug used and the anaesthetic action, studies have shown that there is a correlation between more use of drugs and greater anaesthetic efficacy in the pain management ( 15 ). Authors who evaluated changes in hemodynamic parameters using anesthetics found greater safety when lower volume and concentration of vasoconstrictor were employed ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On other hand, articaine is also an amide local anesthetic with a unique chemical structure. [ 18 ] The presence of thiophene ring in its chemical structure resulted in an increase in lipid solubility and diffusing better through soft tissues than do other anaesthetic, consequently, articaine achieves fast onset time of action along with deep nerve anesthesia. [ 8 ] Articaine is metabolized in the liver, but because of the extra ester bond, it is metabolized by cholinesterase in blood as well.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Articaine is metabolized in the liver, but because of the extra ester bond, it is metabolized by cholinesterase in blood as well. [ 18 19 ] This characteristic is significant, particularly, for patients with liver disease. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%